Adherent-Invasive E. coli: Update on the Lifestyle of a Troublemaker in Crohn’s Disease - Chervy, Mélissa; Barnich, Nicolas; Denizot, Jérémy (International journal of molecular sciences, 2020)
Besides genetic polymorphisms and environmental factors, the intestinal microbiota is an important factor in the etiology of Crohn’s disease (CD). Among microbiota alterations, a particular pathotype of Escherichia coli involved in the pathogenesis of CD abnormally colonizes the intestinal mucosa of patients: the adherent-invasive Escherichia coli (AIEC) pathobiont bacteria, which have the abilities to adhere to and to invade intestinal epithelial cells (IECs), as well as to survive and replicate within macrophages. AIEC have been the subject of many studies in recent years to unveil some genes linked to AIEC virulence and to understand the impact of AIEC infection on the gut and consequently their involvement in CD. In this review, we describe the lifestyle of AIEC bacteria within the intestine, from the interaction with intestinal epithelial and immune cells with an emphasis on environmental and genetic factors favoring their implantation, to their lifestyle in the intestinal lumen. Finally, we discuss AIEC-targeting strategies such as the use of FimH antagonists, bacteriophages, or antibiotics, which could constitute therapeutic options to prevent and limit AIEC colonization in CD patients.